Otitis externa and the use of different antibiotics - Abdelhameed, Buthaina; Sulaiman Erzaiq, Zainab; H. Alanee, Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
A descriptive study , microbiological and pharmacological study was done on hildren with otitis externa 10 years of age and less attending the pediatrics and the Ear Nose and Throat department at the Tikrit Teaching hospitals during the period from 1st of August to 2007 to the last of February 2008. The aim of this study is to evaluate the response of bacteria causing otitis externa to the newly used antibiotics as compared with other old drugs. The total number of cases were 27 cases, males were 21 (77.8% ) while the rest were females, 6 cases (22.2% ). Most of the study cases were between the age of 5-10 years 22 cases (81.5%) .Most of the study cases were from the rural areas 18 cases (66.7%) . Chronic otitis externa is the commonest form of disease in the study cases 25 cases (92.6%) .Most of the study cases have nilateral OE 22 cases (81.5%). Most ofthe cases have infection at the auricle in both male and females, 13 cases (48.1%) and 5 cases (18.5%) respectively. Most ofthe study cases have onset of the disease during summer time , 21 cases (77. 8% ). Most of the study cases had history of swimming 19 cases (70.4% ). All the study cases had history of auricular pain 27 cases (100%), followed by feeling of itching in 16 cases (59.3% All the study cases have tenderness of the external ears specially on moving the pinna 27 cases (100%), followed by swelling of the pinna 16 cases (59.3% ).Staph aureus was the commonest microorganism encountered 18 cases ( 66.7%) followed by pseudomonas Aeruginosa 2 cases (7.4% ). No growth was found in 6 cases (22.2% ). Regarding staph aureus, there is significant response to both erythromycin and to the ciprofloxacin , 18 cases ( 1 00%) and 17 cases (94.4% ) respectively. Regarding the pseudomonas , only the ciprofloxacin and norfloxacin shows response 2 cases for each (100%).the study concludes that the use ofnew regime in the treatment of otitis